Hexokinase-2 depletion inhibits glycolysis and induces oxidative phosphorylation in hepatocellular carcinoma and sensitizes to metformin - Dannielle DeWaal (Nature Portfolio, 2018)
Hexokinase 2 (HK2) is selectively upregulated in hepatocellular carcinoma (HCC). Here the authors show that HK2 ablation decreases glycolysis and triggers oxidative phosphorylation (OXPHO) rendering HCC more susceptible to the OXPHO inhibitor metformin and to the FDA-approved drug sorafenib.